2021
DOI: 10.1097/jnn.0000000000000595
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Affecting Postoperative Delirium in a Neurosurgical Intensive Care Unit

Abstract: PURPOSE: The aim of this study was to identify the prevalence of, and factors affecting, postoperative delirium (POD) in patients in the neurosurgical intensive care unit. METHODS: A cross-sectional study of 127 Turkish neurosurgical intensive care unit patients admitted between May 2018 and May 2019 was conducted. Patients were assessed for the development of POD using the Intensive Care Delirium Screening Checklist. We collected other independent data variables daily. Data were analyzed using independent sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…Current estimates suggest ICU delirium rates range from 18.9% to 83% among diverse cohorts of critically ill patients 2,4,5. Decades of research suggest ICU-acquired delirium is associated with poor clinical outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Current estimates suggest ICU delirium rates range from 18.9% to 83% among diverse cohorts of critically ill patients 2,4,5. Decades of research suggest ICU-acquired delirium is associated with poor clinical outcomes.…”
mentioning
confidence: 99%
“…Current estimates suggest ICU delirium rates range from 18.9% to 83% among diverse cohorts of critically ill patients. 2,4,5 Decades of research suggest ICU-acquired delirium is associated with poor clinical outcomes. In a variety of ICUs, delirium has shown to be an independent predictor of prolonged hospital and ICU length of stay (LOS); 6 higher ICU, 7 hospital, 7,8 and 6-month mortality; 8 prolonged mechanical ventilation; 7 postdischarge disability; 9 and severe long-term cognitive impairment.…”
mentioning
confidence: 99%
“…21,22 Although we found no difference in delirium or confusion based on family presence, our study examined only the first postop night. Although ICU delirium may take up to 72 hours to manifest, 23 Kose et al 5 found that 18.9% of postop neurosurgical patients experience delirium on their first postop day. It is also possible that because confusion and delirium are known to wax and wane, our observation of baseline and first postop day may have failed to capture undetected incidences of delirium or confusion.…”
Section: Discussionmentioning
confidence: 99%
“…Postop occurrence estimates range from 17% to 61% and are higher in the geriatric population 4. Evidence supports that roughly 1 in 5 persons will experience delirium after spinal surgery,5 but this is not well studied in the postop spinal surgical population. Delirium can include hallucinations, confusion, anxiety, neurologic changes, restlessness, lethargy, disrupted sleep, memory loss, difficult concentrating, and unclear speech 6.…”
Section: Introductionmentioning
confidence: 99%
“…With great interest, we read the recent article by Kose et al 1 assessing the prevalence and factors affecting postoperative delirium (POD) in the neurosurgical intensive care unit. Because POD has been significantly associated with adverse outcomes and high costs after neurosurgery, 2 this study has potentially practical implications.…”
Section: To the Editormentioning
confidence: 99%